Constraining the timing of brittle deformation and sedimentation in southern Finland : Implications for Neoproterozoic evolution of the eastern Fennoscandian shield - Elminen, Tuija; Zwingmann, Horst; Kaakinen, Anu (Precambrian Research, 2019)
Sheared sedimentary clay was found in a faulted fracture in crystalline bedrock in a tunnelling site at 60 m depth in southern Finland. Brittle faults are numerous in the Fennoscandian Palaeoproterozoic bedrock, but only some of them have relative age constraints, while absolute ages are nearly lacking. Sedimentary rocks altogether are uncommon in Finland and only sparsely dated by micropaleontological studies. This study reports K-Ar data of fresh, non-weathered authigenic illite and constrains a time framework for the local faulting and sedimentation. The Neoproterozoic Tonian to Cryogenian ages derived from the grains in diminishing grain-size order are c. 967, 947, 809 and 697 Ma. Results indicate that the formation of the extension fracture is related to the collapse of Sveconorwegian orogeny c. 1000 Ma; clay and mature quartz sand were deposited in this extension fracture in shallow water in an intracratonic basin followed by early diagenetic processes and neocrystallization of illite around 967-947 Ma. The Neoproterozoic 1000-700 Ma sedimentation documented in this study is rare in the Fennoscandian shield as a whole. Neocrystallization of authigenic illite in the finest 0.4 and <0.1 pm fractions c. 809-697 Ma ago is interpreted as resulting from reactivation in the fault due to the continental break-up on the western side of the craton as documented by arenite crosscutting relationships. The younger ages may also be attributed to a Caledonian thermal overprint ca. 410 Ma ago that would influence the 967 Ma age if sufficient thermal energy had been present. Peer reviewed